Cavity ringdown refractive index sensor using photonic crystal fiber interferometer - Chan, Chi Chiu (2013)
A refractive index sensor is demonstrated by integrating a photonic crystal fiber (PCF) Mach–Zehnder interferometer (MZI) into a cavity ringdown loop for improved sensitivity. By splicing a short section of PCF between two single-mode fibers and collapsing air holes over a short region at two splicing point, a MZI will be formed. This is due to the coupling between core and cladding modes in the collapsed region. Through determining the decay constants of cavity ringdown curve under varying external refractive index, a minimum detectable refractive index of 7.8 × 10−5 RIU can be achieved.